1993
DOI: 10.1083/jcb.120.5.1187
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytoplasmic division of Xenopus embryo by rho p21 and its inhibitory GDP/GTP exchange protein (rho GDI).

Abstract: Abstract. Evidence is accumulating that the rho family, a member of the ms p21-related small GTPbinding protein superfamily, regulates cell morphology, cell motility, and smooth muscle contraction through the actomyosin system. The actomyosin system is also known to be essential for cytoplasmic division of cells (cytokinesis). In this study, we examined the action of rho p21, its inhibitory GDP/GTP exchange protein, named rho GDI, its stimulatory GDP/GTP exchange protein, named smg GDS, and botulinum ADP-ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
253
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(260 citation statements)
references
References 66 publications
6
253
1
Order By: Relevance
“…The small GTPase Rho (Van Aelst and D'Souza-Schorey, 1997;Hall, 1998) is known to play a critical role in cytokinesis (Kishi et al, 1993;Mabuchi et al, 1993;Drechsel et al, 1997) and localize to the cleavage furrow (Takaishi et al, 1995). In the present study, we found that Rho-kinase also localized to the cleavage furrow, suggesting that Rhokinase binds to Rho in vivo and phosphorylates several proteins during cytokinesis.…”
supporting
confidence: 67%
“…The small GTPase Rho (Van Aelst and D'Souza-Schorey, 1997;Hall, 1998) is known to play a critical role in cytokinesis (Kishi et al, 1993;Mabuchi et al, 1993;Drechsel et al, 1997) and localize to the cleavage furrow (Takaishi et al, 1995). In the present study, we found that Rho-kinase also localized to the cleavage furrow, suggesting that Rhokinase binds to Rho in vivo and phosphorylates several proteins during cytokinesis.…”
supporting
confidence: 67%
“…(19)(20)(21)(22)(23) Rho activity zones are typically spatially confined to regions with widths on the order of microns, while the linear dimension of the cells in which they form ranges from hundreds of microns (Xenopus oocytes, echinoderm zygotes) to tens of microns (echinoderm blastomeres, cultured mammalian cells). Rho itself was shown to be required for cytokinesis long ago, (1) but these findings, and the demonstration that active Rho dynamically senses microtubule perturbation, (18) imply that Rho zones are part of the long-sought link between microtubule geometry and stimulation of cytokinetic furrowing. It remains to be seen whether Cdc42 and/or Rac activity zones also participate in cytokinesis, but this is consistent with several findings.…”
Section: Rho Gtpase Activity Zonesmentioning
confidence: 99%
“…A contribution of Rho in contractile ring formation has been reported previously (Kishi et al, 1993;Mabuchi et al, 1993). However, in fluorescence resonance energy transfer (FRET)-based analysis, it has been concluded that Rho activation is not required for contractile ring formation (Yoshizaki et al, 2003).…”
Section: Introductionmentioning
confidence: 98%